Development in the Anthropocene (UJ Press, 2026)
The pith of this book is interventions to collaboratively better the lives of low-income households with their development on a local scale. These interventions are co-created with communities. Successful interventions to provide more efficient and less polluting energy, treatment of waste, and sanitation are discussed here. Access to water is also discussed. They all contribute to planetary well-being in their small way. These are not the only developmental topics: early childhood development, artificial intelligence, policy-making, urban planning, intervention models, and research tools are also on the table.